I am Tired of Teaching: Relationship between Teachers’ Boredom and Their Psychological Disorders during Covid-19 Pandemic - Ariffudin, Imam; Rahmawati, Ajeng Intan Nur (Jurnal Kajian Bimbingan dan Konseling, 2021)
The continuous practice of online learning potentially carries boredom and negative effects on teachers’ psychology. This study investigates the effects of boredom on teachers’ psychological disorders during online learning. This correlational study used an explanatory design, involving 113 teachers from different educational levels (junior, senior, and vocational schools) in Malang, Indonesia. The participants were selected through cluster random sampling technique. The data collection process was carried out using two standardized instruments, the DASS 21 (Depression, Anxiety, and Stress Scale) and ABS-10 (Academic Boredom Scale). The obtained data were analyzed using correlation and linear regression analysis to examine the relationship and degree of contribution of predictor variable toward the dependent variable. The results indicate that boredom has a significant relationship with teachers’ psychological disorders. The boredom toward the online learning routine is a predictor carrying significant contribution toward teachers’ psychological disorders. The findings conclude that the psychological help and coping strategy enhancement to face boredom are essential for teachers.